Diversity of Entamoeba spp. in Long-tailed Macaque (Macaca fascicularis) in Baluran and Alas Purwo National Parks, Indonesia - DONY CHRISMANTO; Nunuk Dyah Retno Lastuti; LUCIA TRI SUWANTI; POEDJI HASTUTIEK; DYAH AYU KURNIAWATI; CHICI AYU PARAMITA; ADIANA MUTAMSARI WITANINGRUM; ARIF PRATIWI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Chrismanto D, Lastutui NDR, Suwanti LT, Hastutiek P, Kurniawati DA, Witaningrum AM, Paramita CA, Pratiwi A. 2022. Diversity of Entamoeba spp. in Long-tailed Macaque (Macaca fascicularis) in Baluran and Alas Purwo National Parks, Indonesia. Biodiversitas 23: 4524-4531. Entamoeba spp. is one of the most common protozoa in humans and non-human primates. Several species of Entamoeba are considered pathogenic, andone of them is Entamoeba histolytica has become a major public health concern. Contact between humans and Long-tailed Macaques (Macaca fascicularis) in Baluran National Park and Alas Purwo National Park has become more frequent in the last 10 years due to the habit of tourists providing food. This condition increases the potential of zoonoses between humans and Long-tailed Macaques. The aims of this study are to determine the diversity of species of Entamoeba spp. and the potential zoonosis from the Long-Tailed Macaque in Baluran and Alas Purwo National Park. In this study, 200 Fecal samples were collected from Long-tailed Macaques from Baluran National Park (100 samples) and Alas Purwo National Park (100 samples), examined both morphological and molecular examination with Entamoeba genus-specific primer. Positive samples were continued to be examined for the presence of 7 Entamoeba species by PCR amplification of the SSU rRNA gene. The results were found that 53% (53/100) of the samples were identified as Entamoeba spp. from Baluran National Park, and four Entamoeba species were identified, Entamoeba coli 84.9% (45/53), Entamoeba chattoni 58.9% (31/53), Entamoeba hartmanni 7.5% (4/53), and Entamoeba moshkovskii 13.2% (7/53), and among these, 58.49% (31/53) were mixed infections. The results from Alas Purwo National Park showed 82% (82/100) and three species of Entamoeba were detected by molecular tests, E. chattoni (90%), E. coli (85%) and E. moshkovskii (8.5%). The conclusion of the current study revealed the prevalence and diversity of Entamoeba species in Long-tailed Macaques in Baluran National Park and Alas Purwo National Park, Indonesia. This study is the first report on the diversity of Entamoeba species with molecular detection. The risk of zoonosis transmission in the region needs to be closely monitored.